2023
DOI: 10.7769/gesec.v14i3.1802
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in industrial environments: an updated review and a new research agenda

Abstract: Nowadays, discussions about the use of energy efficiency in industries have intensified due to the need to optimize the resources used, especially the high cost in the production process. In this context, a literature review and a research agenda on energy efficiency in industrial environments can assist in the search for solutions and challenges to reduce energy consumption in manufacturing, as well as identify future trends for the topic. Therefore, this article proposes to update the energy efficiency resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
0
2
0
1
Order By: Relevance
“…Penelitian di bidang ini mengeksplorasi berbagai strategi, termasuk penggunaan mesin hemat energi, optimalisasi proses, dan penerapan teknologi pintar (Indraprakoso & Haripin, 2023). Berinvestasi dalam efisiensi energi tidak hanya membantu mengurangi emisi karbon, tetapi juga meningkatkan efektivitas biaya, sehingga menjadi solusi yang saling menguntungkan bagi pelestarian lingkungan dan keberlanjutan ekonomi (Vallarta-Serrano, Santoyo-Castelazo, Santoyo, García-Mandujano, & Vázquez-Sánchez, 2023), (Zhou, Han, & Shen, 2023), (Fenerich, Guedes, Cordeiro, Lima, & De Oliveira, 2023).…”
Section: Langkah-langkah Efisiensi Energiunclassified
“…Penelitian di bidang ini mengeksplorasi berbagai strategi, termasuk penggunaan mesin hemat energi, optimalisasi proses, dan penerapan teknologi pintar (Indraprakoso & Haripin, 2023). Berinvestasi dalam efisiensi energi tidak hanya membantu mengurangi emisi karbon, tetapi juga meningkatkan efektivitas biaya, sehingga menjadi solusi yang saling menguntungkan bagi pelestarian lingkungan dan keberlanjutan ekonomi (Vallarta-Serrano, Santoyo-Castelazo, Santoyo, García-Mandujano, & Vázquez-Sánchez, 2023), (Zhou, Han, & Shen, 2023), (Fenerich, Guedes, Cordeiro, Lima, & De Oliveira, 2023).…”
Section: Langkah-langkah Efisiensi Energiunclassified
“…Noteworthy contributions emphasize the adoption of innovative technologies, process optimization, and resource management strategies as key pillars for enhancing energy efficiency in diverse industrial sectors [11]. Advanced manufacturing technologies, such as the Industrial Internet of Things (IIoT) and artificial intelligence, have revolutionized energy-intensive processes by enhancing operational efficiency and offering avenues for real-time monitoring and adaptive control, thereby optimizing energy utilization [12].…”
Section: Energy Efficiency In Industrymentioning
confidence: 99%
“…This increases the possibilities of decentralized energy supply and the security of operations in a crisis [6]. However, bear in mind that later studies have found that improving energy efficiency is a mandatory requirement for sustainable buildings by adopting measurements such as utilizing renewable energy sources, purchasing energy efficiency systems, using the materials & equipment for CO2 emission reduction, and software for designing the buildings to reach a higher energy efficiency [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%